The role of the root in auditory word recognition of Hebrew. (July 2019) - Oganyan, Marina; Wright, Richard; Herschensohn, Julia
Abstract: Evidence from visual word recognition has shown that the root morpheme plays a particularly important role in recognition of nouns in templatic languages [e.g., Velan & Frost, 2009 (Hebrew), Perea, abu Mallouh, & Carreiras, 2010 (Arabic)]. Letter transposition studies in masked priming have proved a useful tool for investigating letter flexibility in the visual domain. Due to the linear nature of the auditory signal, such manipulation is not possible for spoken words. In this study, we use a novel application of the phonemic restoration paradigm to explore the role of morphology in auditory word recognition. In two separate experiments, we show that in auditory word recognition the root plays an important role in Hebrew noun recognition, with words with masked root sounds being especially difficult to recover. This study provides additional evidence in favor of the privileged role of the root in Semitic lexical access and its function in morphological decomposition.